Iron Absorption and Blood Loss in Patients with Hiatus Hernia. Issue 5609 (6th July 1968) - Holt, J. M.; Mayet, F. G. H.; Warner, G. T.; Callender, S. T.; Gunning, A. J.
Abstract : Iron absorption was measured in 28 patients, 19 of whom were anaemic. The mean absorption in the anaemic patients was 39% and in the non-anaemic patients 8%. Gastrointestinal blood loss was then measured in 26 of these patients. The mean estimated blood loss in the anaemic patients was 15 ml. a day and in the non-anaemic patients 3 ml. a day. In 16 of the 19 anaemic patients symptoms of anaemia were either the sole or the major complaint.